2005
DOI: 10.1021/bi050863a
|View full text |Cite
|
Sign up to set email alerts
|

Transition State Structure of 5‘-Methylthioadenosine/S-Adenosylhomocysteine Nucleosidase from Escherichia coli and Its Similarity to Transition State Analogues

Abstract: Methylthioadenosine/S-adenosylhomocysteine nucleosidase (MTAN) catalyzes reactions linked to polyamine metabolism, quorum sensing pathways, methylation reactions, and adenine salvage. It is a candidate target for antimicrobial drug design. Kinetic isotope effects (KIEs) were measured on the MTAN-catalyzed hydrolysis of 5'-methylthioadenosine (MTA) to determine the transition state structure. KIEs measured at pH 7.5 were near unity due to the large forward commitment to catalysis. Intrinsic KIEs were expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
257
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(265 citation statements)
references
References 45 publications
8
257
0
Order By: Relevance
“…A kinetic isotope effect analysis showed that the enzyme utilizes a highly dissociative mechanism with a transition state that has considerable oxocarbenium ion character (Fig. 3) (28). Mutagenesis and structural studies have shown that there are three conserved residues that are absolutely essential for the activity of this enzyme: Glu-12, Glu-174, and .…”
Section: Resultsmentioning
confidence: 99%
“…A kinetic isotope effect analysis showed that the enzyme utilizes a highly dissociative mechanism with a transition state that has considerable oxocarbenium ion character (Fig. 3) (28). Mutagenesis and structural studies have shown that there are three conserved residues that are absolutely essential for the activity of this enzyme: Glu-12, Glu-174, and .…”
Section: Resultsmentioning
confidence: 99%
“…Alkaline phosphatase was from Roche. Ribokinase and phosphoribosyl-α-1-pyrophosphate synthetase were prepared as previously described (36,37). Hypoxanthine-guanine phophoribosyltransferase was a kind gift from Keith Hazleton of this laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…Studies utilizing kinetic isotope effects (KIEs) and crystal structures of MTANs in complex with known transition state analogues have allowed for transition state modeling of MTANs from E. coli, S. pneumoniae, Neisseria meningitidis, S. aureus, and V. cholerae and the subsequent design of analogue inhibitors (120)(121)(122)(149)(150)(151)(152)(153). Thus far, it appears that most MTANs share a fully dissociated S N 1 transition state characterized by a ribooxacarbenium ion (121,122,149,152), with the exception of MTANs from (149).…”
Section: Inhibition Of Mtansmentioning
confidence: 99%
“…Thus far, it appears that most MTANs share a fully dissociated S N 1 transition state characterized by a ribooxacarbenium ion (121,122,149,152), with the exception of MTANs from (149). The majority of the transition state analogue inhibitor characterization has been performed using purified MTANs in vitro.…”
Section: Inhibition Of Mtansmentioning
confidence: 99%